Prevalence Of Common Hemoglobinopathies in Gujarat: An Analysis of a Large Population Screening Program - Patel , Ashwin P; Naik , Madhuben R; Shah , Nilam M; Sharma , Narmadeshwar P; Parmar , Prakash H (National Journal of Community Medicine, 2012)
Objectives: To determine prevalence and geographical distribution of ß-thalassemia trait and sickle cell trait in Gujarat Methods: The present study includes 3, 17,539 persons who were screened for hemoglobinopathies from September 2004 to November 2008. Blood samples were collected into EDTA and run in coulter AC.T diff 2 TM, electronic analyzer and analyzed on Bio-Rad Variant I HPLC System. Results: The prevalence of ß-thalassemia trait (BTM) and sickle cell trait (SCT) is 1.95% and 6.54% respectively. In tribal area, 1.74% has BTM and 11.37% has SCT trait while in non-tribal area, BTM is seen in 2.18% and 1.1% has SCT. Rathva (18.65%), Nayka (15.38%), Gamit (17.64%), Tadvi (16.95%), Bariya (16.5%), Adivasi (15.25%) and Chaudhary (15.63%) communities have higher prevalence of SCT. BTM is more prevalent in Bhanusali (8.1%), Bhakta (7.93%) and Luhana (6.5%) community. SCT is very common in schedule castes (8.1-10.52 %) and it is seen in many general castes. Conclusion: The prevalence of BTM is 1.95% while SCT is 6.54% in Gujarat. Sickle cell gene frequency is high in tribals (11.37 %) except in Banaskantha (5.12 %) and Sabarkantha (3.43%). Sickle cell is prevalent in all schedule castes and many general castes. ß-thalassemia gene frequency is higher in Sindhi (Bhanusali) and Bhakta communities and in Banaskantha district (4.45%).